Analisis Kesesuaian Lokasi Bendung Kecil dan Daerah Pemanenan Air Hujan (PAH) dengan Menggunakan Sistem Informasi Geogerafis (SIG) di Wilayah Perkotaan - Atep Hermawan; Yanuar Juardi Purwanto; Nora Herdiana Pandjaitan (Diponegoro University, 2020)
Assessment of site suitability for water harvesting in Sentul City is an important, because the Sentul City area often problems with water supply and is expected to prediction a water deficit in 2050, other problems are floods often occur in the downstream during the rainy season. This study aims to analyze the suitability of the location for small dam and reservoirs determine the number of small dam and reservoirs that can be built in Sentul City based on location suitability maps. Identifying locations for the construction of small dam and reservoirs can use of Geographic Information System (GIS), the approach used multi criteria analysis and weighted overlay techniques with software ArcGIS. Six criteria were considered for this study, which include topographic factors (slope), land use, soil texture, rainfall, and distance to the river and distance to the road. The multi criteria analysis approach, each criterion was assigned a weight with slope being considered as the most important factor. Weighted overlay analysis was performed in ArcGIS and determination of suitable small dam and reservoir site was done from the summation of weight of each contributing factor. A final suitability map was generated which indicated that 34% of the total study area showed that the area was not suitable, 31% highly suitable, 27% was suitable, 6% was moderately suitable and 2% was low suitable for dam construction. Based on suitable map, 5 (five) samall dam and 9 (nine) reservoir can be used to water harvesting that can be used as raw water sources in Sentul City.